1985
DOI: 10.1002/jcp.1041240119
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic stimulation of alkaline phosphatase activity in bovine aortic endothelial cells grown in the presence of retinoids and glucocorticoids

Abstract: Low concentrations of retinol (10 nM-10 microM) and dexamethasone (0.1 nM-1.0 microM) elevated activity of alkaline phosphatase (E.C. 3.1.3.1) in bovine endothelial cells in culture. The effect was apparent after 48 hr of growth in the presence of either of the two compounds, prior to any growth stimulatory effects. A synergistic stimulation of alkaline phosphatase was achieved in the presence of both retinol and dexamethasone implying different mechanisms of induction. Retinoic acid and retinyl acetate also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The study also revealed strongly down-regulated expression of the bone TNAP transcript when mouse BCECs were maintained in solo-culture for a few days [61]. Interestingly, a variety of molecules are known to modulate AP expression (retinoic acid [62][64]; cAMP [65]; glucocorticoids [62], [66]; transforming growth factor-beta [53]; IL-6 [53] and basic fibroblast growth factor [54], [67]) and brain capillary endothelial permeability. In the present study, we found that glial-cell-induced TNAP expression prevented a levamisole-induced increase in endothelial permeability - suggesting a protective effect.…”
Section: Discussionmentioning
confidence: 84%
“…The study also revealed strongly down-regulated expression of the bone TNAP transcript when mouse BCECs were maintained in solo-culture for a few days [61]. Interestingly, a variety of molecules are known to modulate AP expression (retinoic acid [62][64]; cAMP [65]; glucocorticoids [62], [66]; transforming growth factor-beta [53]; IL-6 [53] and basic fibroblast growth factor [54], [67]) and brain capillary endothelial permeability. In the present study, we found that glial-cell-induced TNAP expression prevented a levamisole-induced increase in endothelial permeability - suggesting a protective effect.…”
Section: Discussionmentioning
confidence: 84%
“…Changes in the specific activity of alkaline phosphatase are not therefore due to a stimulation or inhibition of cell growth by these compounds. Adams and Melnykovych (1985) have shown that dexamethasone increased the alkaline phosphatase activity in bovine endothelial cells, but they concluded that the steroid was not acting via a receptor-mediated mechanism. In the LEII mouse endothelial cell line used in the …”
Section: Discussionmentioning
confidence: 95%
“…The study revealed strongly down-regulated expression of the bone TNAP transcript when mouse BCECs were maintained in solo-culture for a few days (Brun-Heath et al 2011). Interestingly, a variety of molecules are known to modulate TNAP expression [retinoic acid (Zhou et al 1994;Lechardeur et al 1995); cAMP (Beuckmann et al 1995); glucocorticoids (Adams and Melnykovych 1985;Mulkins and Allison 1987); transforming growth factor-beta (Nakazato et al 1997); IL-6 (Nakazato et al 1997) and basic fibroblast growth factor (Roux et al 1994;Sobue et al 1999)] (see also Chap. 4) and brain capillary endothelial permeability.…”
Section: Bbb-phenotype Induction By Surrounding Cellsmentioning
confidence: 91%